Factors associated with death places among elderly patients receiving home-based care. Issue 30 (29th July 2022) - Chiang, Jui-Kun; Kao, Yee-Hsin
Abstract : The quality of end-of-life (EOL) care for patients receiving home-based care is a critical issue for health care providers. Dying in a preferred place is recognized as a key EOL care quality indicator. We explore the factors associated with death at home or nursing facilities among elderly patients receiving home-based care. This retrospective study was based on a medical chart review between January 2018 and December 2019 of elderly patients. Multivariate analysis was conducted by fitting multiple logistic regression models with the stepwise variable selection procedure to explore the associated factors. The 205 elderly patients receiving home-based care were enrolled for analysis. The mean participant age was 84.2 ± 7.8 years. Multiple logistic regression indicated that significant factors for elderly home-based patients who died at home or nursing facilities were receiving palliative service (odds ratio [OR], 3.21; 95% confidence interval [CI], 1.37–7.51; P = .007), symptoms of nausea or vomiting (OR, 5.38; 95% CI, 1.12–25.84; P = .036), fewer emergency department visits (OR, 0.07; 95% CI, 0.03–0.16; P < .001), and less intravenous third-generation cephalosporin use (OR, 0.15; 95% CI, 0.03–0.75; P = .021) in the last month of life. Patients with dementia had a lower probability of dying at home or nursing facilities than patients with other diagnosis (OR, 0.34, 95% CI, 0.13–0.90; P = .030). Among elderly home-based patients, receiving palliative service, with nausea or vomiting, and fewer emergency department visits in the last month of life favored home or nursing facilities deaths. Practitioners should be aware of the factors with higher probabilities of dying at home and in nursing facilities. We suggested that palliative services need to be further developed and extended to ensure that patients with dementia can receive adequate EOL care at home and in nursing facilities.